2006
DOI: 10.1002/hup.755
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 genotype‐associated differences in the acute effects of alcohol on P300, psychomotor performance, and subjective response in healthy young Korean men: a double‐blind placebo‐controlled crossover study

Abstract: These results suggest that the ALDH2 polymorphism is an important factor in determining the effects of alcohol on various psychobehavioral functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…A previous study on Health Risk Appraisal Models, which made use of information on ALDH2 variants to evaluate disease outcomes, supported this notion, showing high detection rate 67. In line with this, the inclusion of genetic information is now regarded as a very useful tool for educating alcohol intake and drinking behavior properly in community and/or clinical settings,68 yet still, such a genetic education model is not available in Korea.…”
Section: A Genetic Education Model For Alcohol Consumption and Relatementioning
confidence: 86%
“…A previous study on Health Risk Appraisal Models, which made use of information on ALDH2 variants to evaluate disease outcomes, supported this notion, showing high detection rate 67. In line with this, the inclusion of genetic information is now regarded as a very useful tool for educating alcohol intake and drinking behavior properly in community and/or clinical settings,68 yet still, such a genetic education model is not available in Korea.…”
Section: A Genetic Education Model For Alcohol Consumption and Relatementioning
confidence: 86%
“…All subjects consumed the test or placebo beverages in random sequence over the three time points (with an interval of a week for three consecutive weeks). Each beverage was made to a volume of 500 ml and consumed over 10 min at room temperature from an opaque bottle, through a stopper packed with spirit soaked cotton wool, to provide olfactory masking (Shin et al, 2006). The timetable for each evaluation session is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The ethnicity difference is important for studying the risk of developing OUD and the treatment outcomes [55,56]. Unfortunately, other studies focused only on the effects of ALDH2 gene polymorphisms in modulating alcohol-related cognitive function [19,20] and ignored the changes caused by other classes of substance abuse. Kim et al [19] found that the psychomotor performance of patients with ALDH2*1/*2 was significantly poorer than that of those with the ALDH2*1/*1 genotype after alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ALDH2 polymorphisms are associated with the effects of alcohol on various neurophysiological and psychomotor functions [19,20]. All these studies [17][18][19][20] hypothesized that the ALDH2 gene polymorphisms affect aldehyde metabolism and cognitive function. We therefore hypothesize that the ALDH2 gene affects the cognitive functions in patients with OUD as it does in alcohol abusers, and that it leads to the underlying cognitive deficits in OUD.…”
Section: Introductionmentioning
confidence: 99%